Environmental release of non-Aroclor polychlorinated biphenyls by a silicone rubber production site did not lead to elevated plasma levels in the nearby population - Kaifie, Andrea; Esser, André; Ziegler, Patrick; Kraus, Thomas; Rauchfuss, Knut; Schettgen, Thomas (International Journal of Hygiene and Environmental Health, 2022)
In 2019, high concentrations of the non-Aroclor PCB congeners 47, 51, and 68 were released by a silicone rubber production site in North-Rhine Westphalia, Germany. Local authorities announced a consumption alert for home-grown fruits and vegetables for the affected area which led to a great level of insecurity among the population regarding potential health effects. The aim of study was to determine the plasma levels of the non-Aroclor congeners and the six ndl-indicator congeners (PCB 28, 52, 101, 138, 153, 180) in children and women with child-bearing potential living close to the production site. Altogether n = 111 participants, with n = 73 female adults and n = 38 children were included in this analysis. For the non-Aroclor-PCBs as well as the lower-clorinated ndl-indicator PCBs 28, 52, and 101, the median plasma concentrations were below the LOQ. Only one adult showed an elevated PCB 47 value. In conclusion, no elevated plasma levels could be detected for PCB 47, 51, or 68 in the nearby population of the silicone-rubber production site. However, our study was highly important for risk characterisation as well as risk communication.
CRIS-Team Scopus Importer:2023-09-25
Keywords: Biological monitoring; Exposure assessment; PCB; Persistent organic pollutants